Factors Governing Organic Amendments and NPK Fertilizers Effects on Sweet Maize in Old and Intensively Cultivated Experimental Farm - Heru Bagus Pulunggono; Moh Zulfajrin; Lina Lathifah Nurazizah (Faculty of Agriculture, Tompotika Luwuk University, 2023)
Applying organic amendment (OA) containing humic compounds (HC) and phytohormones is a promising solution to intensify sustainable food production under increasing global food needs, declining environmental carrying capacity and changing climate. However, most positive claims on OA efficacy often came from controlled, greenhouse experiments. The field trial was conducted on an intensively cultivated experimental farm station, Department of Soil Science and Land Resources, Faculty of Agriculture, IPB University. The OA testing was done on sweet maize (Zea mays L. saccharata) using a fractional factorial randomized block design by comparing five rates of the organic amendment (0, ½, 1, 1½, and 2 standards OA) with three rates of NPK fertilizer (0, 1, and ¾ standards NPK). The results revealed that a single OA application did not significantly boost the growth and biomass of sweet maize, especially when applied to an old and intensively cultivate and organically manured farm. OA had significant interaction with NPK at most of the yields and biomass parameters. Amending soils more than 12 L OA ha-1 could improve the sweet maize’s growth and development while saving 25% NPK fertilizers. Linear mixed effect model and multivariate analysis uncovered higher heterogeneity in trial plots controlled maize growth, biomass, and agronomic effectivity, regardless of the given treatments. This study highlighted three important marks for future research: (1) soil plowing, harrowing and mixing must be intensively done across plots, (2) adequate HC contents must be increased from the OA current rate, and (3) the greater role of phytohormone in stimulating maize growth and production at the OA current rate.